Low expression of TCP1 (T-Complex 1) and PSMC1 (Proteasome 26S subunit, ATPase 1) in heterotopic ossification during ankylosing spondylitis. Issue 1 (1st January 2021) - Zhong, Xiao-lin; Qian, Bang-Ping; Huang, Ji-chen; Zhao, Shi-zhou; Li, Yao; Qiu, Yong
ABSTRACT: Heterotopic ossification (HO) is frequently seen in patients with spinal injuries. Therefore, this study aimed to characterize the association of HO with ankylosing spondylitis (AS) through gene expression profiling. The human transcriptomic datasets (GSE73754 and GSE94683) were obtained from the Gene Expression Omnibus database for analysis. Overlapping differentially expressed genes (DEGs) were identified between AS and HO disease states. Subsequently, weighted gene co-expression network analysis (WGCNA) was performed for constructing and identifying hub genes for each condition. Finally, a consensus of the overlapping DEGs and the hub genes in AS and HO was taken for determining the key genes involved in AS-induced HO. Quantitative real-time polymerase chain reaction and western blotting were used to detect the mRNA and protein expression levels in mesenchymal stem cells of AS patients and controls. Additionally, immunohistochemistry was performed on interspinous ligament samples for experimental validation of genes. DEG analysis identified 355 overlapping genes between HO and AS. WGCNA indicated that the salmon module of the 22 modules constructed, was most significantly correlated with AS-induced HO. Subsequently, Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analysis of the salmon module indicated the presence of genes enriched in proteasome regulatory particle and proteasome pathways. mRNA expression analysis identified TCP1 and PSMC1 as the key genes in AS-induced HO. Further validation of these genes could help elucidate their role in the complex association of AS and HO.